(untitled) (Journal of the College of Education for Women, 2019)
Community participation is one of the basic pillars of the sustainable development process. It provides opportunities for different groups of society to contribute to the management, preparation and implementation of development plans commensurate with their needs and aspirations. In this context, the study presents a study of the concept of community participation and its importance in sustainable development, In terms of its conditions, requirements and principles, as well as its image, as well as addressing the most important challenges and obstacles facing the participation of citizens in development projects. The research also provides an analysis of a number of international and Arab experiences adopted In its policies to implement the idea of ​​community participation to achieve sustainable development by enabling the community to play an active role in all stages of the development process. The research concluded that the promotion of community participation in sustainable development gives the marginalized groups in social development and advancement through the role they play in Activating the dynamics of sustainable development.